Managerial Analysis of the Implementation of the Standard Inpatient Class (KRIS) Policy in BPJS Services - Andi Kurniawan; Saparuddin Latu; Mustamin (Indonesian Health Issue, 2026)
Background: The implementation of the Standard Inpatient Class (KRIS) policy is part of the National Health Insurance (JKN) transformation aimed at improving equity and quality of inpatient services for BPJS Health participants. Objective: This study aimed to analyze the effect of hospital managerial functions on KRIS policy implementation and BPJS patient satisfaction, as well as to examine the mediating role of KRIS implementation at RSUD dr. Kanujoso Djatiwibowo Balikpapan. Methods: This study employed a quantitative approach with an explanatory research design. The research was conducted at RSUD dr. Kanujoso Djatiwibowo Balikpapan in 2026 involving 100 BPJS inpatients selected through purposive sampling. Data were collected through questionnaires, observations, and documentation, and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. Results: The findings revealed that Hospital Management significantly affected BPJS Patient Satisfaction (β = -0.954; p < 0.001) and KRIS Policy Implementation (β = 0.799; p < 0.001). KRIS Policy Implementation also had a positive and significant effect on BPJS Patient Satisfaction (β = 1.358; p < 0.001). The R-Square values indicated that the model explained 68.4% of the variance in BPJS Patient Satisfaction and 63.8% of the variance in KRIS Policy Implementation. Furthermore, KRIS Policy Implementation was proven to act as a mediating variable with an indirect effect value of 1.085. Conclusion: KRIS policy implementation plays an important role in strengthening the influence of hospital managerial functions on BPJS patient satisfaction. Therefore, hospitals should strengthen managerial functions, improve facility readiness, and conduct continuous evaluations of KRIS implementation to enhance service quality and patient satisfaction.